Media Sosial, Impulsive Buying, dan Etika Konsumsi Islam Berbasis Qana‘ah - Desy Bariyyatul Qibtiyah; Hawiwin Fitriah (ARBITRASE: Journal of Economics and Accounting, 2026)
Social media such as TikTok, Instagram, and Shopee encourage impulsive buying among students at the Nurul Jadid University (UNUJA) religious Islamic boarding school in Probolinggo. Through FOMO (fear of missing out) tactics, viral content, and viral discounts, this contradicts Islamic consumption ethics based on qana'ah (contentment), an attitude of satisfaction and sufficiency with Allah SWT's sustenance. Data were obtained through in-depth interviews, observation, and documentation of 15 students selected using a purposive sampling technique. Data analysis was conducted through source triangulation with member checking techniques to ensure the reliability and validity of the findings. The research findings indicate that 13 of the 15 students have made unplanned impulsive purchases after being exposed to content on social media, triggered by visual appeal, discount offers, the influence of influencers, and easy access to digital transactions. Although some students are beginning to recognize the negative impacts, the practice of qana'ah values ??is still not fully visible in real attitudinal changes. This study addresses the limited lack of spiritual research in the context of modern Islamic boarding schools and supports the development of Islamic character education in the digital era. This study fills the gap in spiritual studies that is limited to the context of contemporary Islamic boarding schools and supports the development of Islamic character education in the digital era. Academically, this research contributes by expanding the study of impulsive buying through the perspective of contentment (qanaah) in the context of Islamic boarding school students. Practically, these findings can serve as a basis for strengthening Islamic character education and digital literacy, enabling students to better manage their consumption in the social media era.